COSMOPOLITAN COMMUNICATION BEHAVIOR AMONG AGRICULTURAL EXTENSION WORKERS IN THE USE OF INFORMATION MEDIA IN THE DIGITAL ERA AT CIANJUR DISTRICT - Utami, Atikah Dewi; Alrajabi, Prastowo (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The digital era has fundamentally brought changes to various agricultural extension activities in carrying out communication activities. As is well known, extension agents as communication managers who serve as development agents are required and actively seeking information. The process seeking extension agent information is related to the media used and the cosmopolitan of the extension agents in dealing with information sources outside the village. This paper that the result of research that aims to describe the cosmopolite communication behavior of agricultural instructors and analyze the factors related to the cosmopolitan communication behavior of agricultural instructors in the digital era. The research location is in Cianjur District North Region, West Java. The research method used was a survey with a purposive sampling method of 5 UPTDs located in the North Region, obtained a sample of 80 extension workers. Data collection used questionnaires as primary data and in-depth interviews with related agencies as secondary data. The score calculation uses by analyzing the data to measure the level of cosmopolite communication behavior of the extension agents and the factors related to the cosmopolitan communication behavior of the extension agents. The results showed that the cosmopolite communication behavior of the extension agents in seeking information outside the village was still moderate. Then, age and years of service negatively correlated with the cosmopolitan communication behavior of the extension agents. It proves that the longer the extension worker works and the older the extension worker is, it does not indicate a cosmopolitan position of the extension agent in seeking information outside the village. Print media and electronic media are still the means of extension agents seeking information through the media, which is indicated by the research results that the accessibility of print and electronic media that positively correlated with the instructor's cosmopolite communication. Keywords : Communication Behaviour, Agricultural Extension, Digital Era